2020
DOI: 10.1007/s00280-020-04061-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the immunoproteasome as a potential therapeutic target in cisplatin-resistant small cell and non-small cell lung cancer

Abstract: We evaluated the expression of proteasome subunits to assess whether the proteasome could be a therapeutic target in cisplatin-resistant lung cancer cells.Methods: Cisplatin-resistant (CR) variants were established from three non-small cell lung cancer (NSCLC) cell lines (A549, H1299, and H1975) and two small cell lung cancer (SCLC) cell lines (SBC3 and SBC5). The expression of proteasome subunits, the sensitivity to immunoproteasome inhibitors, and 20S proteasomal proteolytic activity were examined in the CR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Tetsuaki Shoji et al found that in cisplatin-resistant lung cancer cell line models, the transcription levels of PSMB8 and PSMB9 were highly expressed, and the protein expression levels were also significantly increased. After treatment with immunoproteasome inhibitors, it was found that immunoproteasomes may be an effective therapeutic target for some cisplatin-resistant lung cancers [ 47 ]. STAT1 is a signal transducer and activator of transcription 1, a member of the STAT protein family [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tetsuaki Shoji et al found that in cisplatin-resistant lung cancer cell line models, the transcription levels of PSMB8 and PSMB9 were highly expressed, and the protein expression levels were also significantly increased. After treatment with immunoproteasome inhibitors, it was found that immunoproteasomes may be an effective therapeutic target for some cisplatin-resistant lung cancers [ 47 ]. STAT1 is a signal transducer and activator of transcription 1, a member of the STAT protein family [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunoproteasome is an isoform of the constitutive 20S proteasome that becomes expressed when cells are stressed or in response to interferon-gamma and has recently become an attractive therapeutic target in some solid tumors. 46 , 47 We observed protein expression increases in all three immunoproteasome subunits (PSMB8, PSMB9, and PSMB10) by each ADCC-resistant cell line ( Figure 6a ). These increases in subunit expression resulted in significant upregulation of immunoproteasome protein cleavage activity which could be inhibited by the irreversible immunoproteasome-specific compound ONX-0914 ( Figure 6b ).…”
Section: Adcc Selection Pressure Activates the Immunoproteasomementioning
confidence: 92%
“…Treatment of cisplatin-resistant tumor cells with proteasome inhibitors led to apoptosis induction, cell cycle arrest, and mitotic catastrophe. The authors propose that upregulation of immunoproteasome expression was a response to circumvent the cellular stress induced by cisplatin treatment [ 158 ]. Sensitivity to proteasome inhibitors by tumor cells was found to be associated with immunoproteasome subunit expression.…”
Section: Functional and Mechanistic Role Of Immunoproteasome Subunits In Cancermentioning
confidence: 99%
“…The regulation of catalytic βi-subunits in cancer is brought about by several mechanisms. As described, NFκB, mTOR, and STAT1 have been shown to regulate the expression of PSMB8 in colon and lung cancer [ 154 , 157 , 158 ]. In acute promyelocytic leukemia (APL), the fusion transcription factor PML/RARα resulting from the causative chromosomal rearrangement (15;17) has been shown to interact with transcription factor PU.1 to repress the expression of all βi subunits [ 164 ].…”
Section: Functional and Mechanistic Role Of Immunoproteasome Subunits In Cancermentioning
confidence: 99%